The impact of cash holdings on financial performance: Evidence from Iraq - Al-Sulayvani, Nareen Ibrahim Musto; Saeed, Nawzad Khudhur; Ismail, Basheer Yousif; Ahmed, Younus Abdulkareem (Asian Economic and Financial Review, 2025)
The research paper aims to identify the effect of cash holdings on the financial performance of companies on the Iraqi Stock Exchange over a five-year period (2019–2023), as well as the correlation between cash holdings and financial performance. To achieve the research’s objectives, an applied approach was adopted to evaluate the variables and analyze them using statistical tools on data collected from the Iraqi Stock Exchange for (16) companies using the program (E-views12). Through multiple linear regression equation coefficients, we test the main hypothesis of the study. The main conclusion of the study was that holding cash has a positive effect on the financial performance of companies listed on the Iraqi Stock Exchange. It also shows that holding a lot of cash in Iraq helps companies take advantage of profitable investment opportunities that may come up in the future, which also improves their financial performance. This suggests that maintaining high levels of cash holding helps companies in the Iraqi context to capitalize on profitable investment opportunities that may arise in the future, thereby improving their financial performance.